2019
DOI: 10.1111/jce.14288
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and clinical outcomes of inappropriate sinus tachycardia

Abstract: Background: Limited data are available regarding the demographics, disease associations, and long-term prognosis of patients with inappropriate sinus tachycardia (IST).Objective: To establish epidemiologic data for patients with IST, including symptom onset, comorbid disease, and long-term outcomes. Methods:We retrospectively reviewed all patients with an IST diagnosis at the Mayo Clinic (Rochester, MN) during a 20-year period . We extracted demographic data and clinical outcomes compared to an age and gender-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
1
17
0
3
Order By: Relevance
“…A high number of women in our cohort received therapy for anxiety and/or other psychiatric conditions. This is in line with findings from other studies reporting high rates of anxiety (25%) and depression (26%) in IST patients [25]. Anxiety is considered as non-cardiac symptom of inappropriate sinus tachycardia, and vice versa, anxiety may trigger tachycardia.…”
Section: Treatment Indicationssupporting
confidence: 92%
See 1 more Smart Citation
“…A high number of women in our cohort received therapy for anxiety and/or other psychiatric conditions. This is in line with findings from other studies reporting high rates of anxiety (25%) and depression (26%) in IST patients [25]. Anxiety is considered as non-cardiac symptom of inappropriate sinus tachycardia, and vice versa, anxiety may trigger tachycardia.…”
Section: Treatment Indicationssupporting
confidence: 92%
“…Preconception counselling is of utmost importance in all women considering pregnancy under medication [27]. Sinus tachycardia is a condition diagnosed mainly in young females and the first diagnosis is frequently made during or after pregnancy [25]. Considering the increasing off-label use of ivabradine as well as the high rate of > 40% unplanned pregnancies [28], more exposed pregnancies can be expected in the future.…”
Section: Treatment Indicationsmentioning
confidence: 99%
“…Most patients with inappropriate sinus tachycardia are young and female. Among a single-center cohort of 305 patients with inappropriate sinus tachycardia seen between 1998 and 2018, 92% were female, with an average age of 33 years [ 8 ]. Affected patients have an elevated resting heart rate and/or an exaggerated heart rate response to exercise that is out of proportion to their body’s physiological needs; many patients have both.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that anxiety and depression might be responsible, at least in part, for the resting palpitations symptoms in recovered COVID-19 patients. Importantly, a recent retrospective study from Mayo Clinic showed that anxiety and depression are the most common comorbid conditions in patients with inappropriate sinus tachycardia 25 , proposing a possible link between psychological distress and sinus tachycardia.…”
Section: Discussionmentioning
confidence: 99%